Potential hazards and risk identification of safety and health in iron fabrication area of building construction project - Zulhayudin, Muhammad Fadillah; Razzak, Abdul (Universitas Ahmad Dahlan, 2023)
Background: Hazard is a threat to the safety and health of workers. Iron fabrication as an iron work area to cut, bend, and assemble irons which will be used for building construction structures is not an exception for hazards. Preliminary observation has shown a number of hazards which were interesting to be identified further. This study aims to identify hazards in an iron fabrication area. It might be used as a basis to evaluate risks and decide appropriate control determinants. Method: The type of this study was a descriptive survey with an observational approach. The method applied in the study was a Walkthrough Survey using hazard identification sheets as the instruments. Hazard identification was conducted based on UURI Nomor 1 Tahun 1970 (RI Law, 1970) and PPRI Nomor 50 Tahun 2012 (RI Government Regulation, 2012), i.e. by identifying hazards coming from humans, production materials, tools, machinery, work methods, and work environment. Results: Unsafe action; Corroded iron coated with silica; Use of pliers, bending machine, cutting machine, grinder; Repetitive movements of manual handling, awkward body postures; Vibration, noise, heat pressure, dust, fecal coliform, mosquitos, centipedes, and scattered iron cuttings were some of the identified hazards. Conclusion: Every hazard has its own risk whose extent has not been evaluated in this study. In addition, control determinants have not been elaborated. Therefore, further studies are required to evaluate the risks and decide the control determinants based on the hazards which have been identified in this study.